Emotional gaming - Madeira, A.; Arriaga, P.; Adrião, J. G.; Lopes, R.; Esteves, F. (Emotional gaming, 2013)
In recent years, research on the psychology of gaming has examined the negative and positive outcomes of playing video games. Thus far, a variety of affective phenomena have been investigated. In this chapter we will continue this exploration by examining the emotions elicited by the act of playing video games. Because the study of emotions must rely on different type of methods, including subjective self-reports (e.g., description of feelings), neuropsychophysiological measurements (e.g. electromyography, skin conductance, heart rate, event-related potentials, functional magnetic resonance imaging), biological markers (e.g. cortisol, testosterone) and behaviours (e.g., facial expressions), we will cover all these distinct methods. We will explore how dimensional and categorical models of emotions have been used to identify the emotional responses of players, including their enjoyment experience. Expanding upon past research findings we will also discuss the social implications of gaming and suggest areas for future research.